MANAJEMEN OPERASIONAL PELAYANAN KESEHATAN HIV/AIDS PADA PUSKESMAS - Huriati, Huriati; Serang, Serlin; Ramlawati, Ramlawati; Suriyanti, Suriyanti; Alam, Nur; Hidayah, Nur (Jurnal Kesehatan, 2021)
HIV/AIDS spread is a serious threat to human life. Prevention efforts must be carried out in an integrated, effective, and efficient manner in the management of the health service system, beginning with the puskesmas. However, the literature and research findings on the operational management of HIV/AIDS services, which are primarily in the puskesmas, are still scant. This study utilized a descriptive narrative approach with a literature review. According to the findings of a literature review, the Operational Management System for HIV/AIDS services at the puskesmas is regulated in government policies in the process of controlling HIV/AIDS transmission and is carried out with several processes and stages that are regulated in a system with the goal of improving the quality of services for HIV/AIDS patients. Although there are still some obstacles to the service system’s implementation at the puskesmas as a first-rate (Primary) service facility and reduce the rate of HIV/AIDS transmission